2020
DOI: 10.37616/2212-5043.1007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiopulmonary bypass perfusion temperature on perioperative renal function in adult patients undergoing cardiac surgery

Abstract: Aims and objective The primary objective of this investigation was to study the effects of cardiopulmonary bypass (CPB) perfusion temperature on renal function parameters [serum creatinine, creatinine clearance, urine albumin, urine protein, and urine albumin/creatinine ratio (ACR)]. The secondary objective was to detect renal complications of CPB. Materials and methods This is a prospective longitudinal study of 30 adult patients (17 men, 13 women; mean age, 53.37 ± 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…[64,65]. Prior research suggests that optimal brain protection temperatures range from 32 to 34 degrees Celsius, while kidney protection is best achieved between 28 and 32 degrees Celsius [66][67][68][69]. In this study, we have grouped temperatures in two-degree intervals to illustrate the relationship between decreased temperature and increased tissue damage, mindful of the 32-degree boundary.…”
Section: Discussionmentioning
confidence: 99%
“…[64,65]. Prior research suggests that optimal brain protection temperatures range from 32 to 34 degrees Celsius, while kidney protection is best achieved between 28 and 32 degrees Celsius [66][67][68][69]. In this study, we have grouped temperatures in two-degree intervals to illustrate the relationship between decreased temperature and increased tissue damage, mindful of the 32-degree boundary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that prolonged cardiopulmonary bypass time and ACC time were also independent risk factors for postoperative complications of AKI in patients undergoing ONCAB [ 22 , 23 ]. Since renal blood flow and perfusion are relatively insufficient during extracorporeal circulation, massive erythrocytes were destroyed, and the released free hemoglobin consequently caused tubular obstruction and reduced glomerular rate filtration.…”
Section: Discussionmentioning
confidence: 99%